2019
DOI: 10.3390/ijms20030526
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transient Receptor Potential (TRP) Channels in the Transduction of Dental Pain

Abstract: Dental pain is a common health problem that negatively impacts the activities of daily living. Dentine hypersensitivity and pulpitis-associated pain are among the most common types of dental pain. Patients with these conditions feel pain upon exposure of the affected tooth to various external stimuli. However, the molecular mechanisms underlying dental pain, especially the transduction of external stimuli to electrical signals in the nerve, remain unclear. Numerous ion channels and receptors localized in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 269 publications
(673 reference statements)
8
59
0
3
Order By: Relevance
“…Odontoblasts deposit calcium matrix at the outer surface of tooth pulp to form the dentin layer. Due to this anatomical location, the potential secondary role of odontoblasts as a member of the sensory system has been continuously proposed [3,21,22,66,67,68,69,70,71,72,73,74]. The expression of temperature-sensing TRP channels in odontoblasts has been investigated by several researchers, but the results have been diverse.…”
Section: Thermo-sensitive Ion Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Odontoblasts deposit calcium matrix at the outer surface of tooth pulp to form the dentin layer. Due to this anatomical location, the potential secondary role of odontoblasts as a member of the sensory system has been continuously proposed [3,21,22,66,67,68,69,70,71,72,73,74]. The expression of temperature-sensing TRP channels in odontoblasts has been investigated by several researchers, but the results have been diverse.…”
Section: Thermo-sensitive Ion Channelsmentioning
confidence: 99%
“…However, this belief was challenged by multiple observations that pulpal nerves possess physical and chemical properties of large myelinated Aβ fibers. Due to these paradoxical findings, a new concept of “algoneurons” was introduced [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AEA can also activate TRPV1 channels [40]. TRPV1 is implicated in processing of various types of pain including neuropathic and inflammatory pain [182,[190][191][192]. TRPV1 channels are easily desensitized by TRPV1 agonists (e.g., capsaicin) [193].…”
Section: Modulation Of Endocannabinoids Under Neuropathic Pain Conditmentioning
confidence: 99%
“…bradykinin, prostaglandins), anandamide, arachidonic acid metabolites, lipoxygenase products, adenosine, and ATP [6][7][8][9][10]. TRPV1 plays an important role in transduction of pain under physiological and pathological conditions including neuropathic pain (NP) conditions [11][12][13][14][15][16][17][18][19][20][21]. Immunohistochemical studies revealed that the expression profile of TRPV1 changes under NP conditions [12][13][14][15]17,19].…”
Section: Introductionmentioning
confidence: 99%